PELATIHAN PEMBUATAN HANDSANITIZER UNTUK PENCEGAHAN PENULARAN VIRUS COVID – 19 DI DESA LAMPAR, TAMANSARI, BOYOLALI - ICHWAN MUNASIR; MARGARETHA PRABA AULIA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
The outbreak of the Covid 19 pandemic in Indonesia has caused various aspects of the problem. According to data released by the task force for the acceleration of handling of COVID-19, the number of confirmed positive cases reached 1,476,452 with 39,983 deaths. People are encouraged to always maintain health and hygiene, including diligently washing their hands with running water and soap as the number of confirmed cases of Covid 19 increases. The author took the initiative to make an antiseptic handsanitizer liquid made from lime which contains useful chemical elements including citric acid, amino acids, essential oils, glucosides, citric acid and alcohol which are very effective at killing germs and triloxane is an ingredient for making soap. The method used in this study is qualitative research methods qualitative research methods are descriptive research and tend to use analysis. The results of the dedication carried out by the Boyolali University Community Service Program in Lampar Village, Tamansari sub-district, Boyolali Regency have gone well and received a good reception from the local community